Water polo throwing velocity and kinematics: differences between competitive levels in male players - Melchiorri, G.; Viero, V.; Triossi, T.; De Sanctis, D.; Padua, E.; Salvati, A.; Galvani, C.; Bonifazi, M.; Del Bianco, R.; Tancredi, V. (The Journal of Sports Medicine and Physical Fitness, 2016)
AIM: In water polo, throwing is one of the most important and frequently used technical skills for the player. There is no scientific literature that provides information about differences in throwing between elite and sub-elite water polo players. The aim of our study was to study differences in throwing velocities and kinematic variables in elite and sub-elite level male water polo players.